Suggestive Evidence of Slc2a9 Polymorphisms Association in Gouty Malay Males - A, Mahfudzah; MY, Nazihah; WG, Wan Syamimee; T, Huay Lin; WT, Wan Rohani (IIUM Medical Journal Malaysia, 2015)
Introduction: Solute carrier family 2, member 9 (SLC2A9) is thought to be an important urate transporter that influences the excretion and reabsorption of serum uric acid, thus has a strong effect on serum urate and risk of gout. SLC2A9 polymorphisms have been extensively studied in various populations in association with gout development. Our aim was to test for association of SLC2A9 SNPs with gout in Malay males. Methods: 78 gouty patients and 82 normal subjects were recruited and genotyped for rs3733591, rs5028843 and rs11942223 using PCR-RFLP technique. Single association and haplotype association analyses were conducted using SHEsis online software. Results: rs3733591 and rs5028843 showed association with gout with p value of 0.020 and 0.036, respectively, whilst rs11942223 yielded no association with p value of 0.08 with trend towards susceptibility projecting by OR=3.547, 3.667 and 2.732, respectively. It is noteworthy that haplotype 1/1/1 conferred protection in gout with p value 0.004 (OR=0.324 [0.147-0.716]). Conclusion: This study might suggest an evidence of association of SLC2A9 SNPs with gout among Malay males.